2011
DOI: 10.3109/09537104.2011.560305
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of human platelet microRNA by quantitative PCR coupled with an annotation network for predicted target genes

Abstract: Platelets are anucleate blood cells that play a crucial role in thrombosis and hemostasis. Despite their lack of nuclear DNA, platelets contain significant amounts of microRNA (miRNA) that may have vital functions in post-transcriptional gene regulation. Here, we combined comprehensive miRNA expression profiling by quantitative PCR with target prediction analysis for the most abundant miRNAs in human platelets. A network composed of predicted platelet miRNA target genes was then constructed, using annotations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
83
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 33 publications
10
83
0
Order By: Relevance
“…Although this result is in alignment with a study done in 2009 by Landry et al (23) which showed that mRNA translation in blood platelets is regulated by miRNA and that different miRNAs was described to affect biosynthesis of platelets like miR-15 a, miR-339-3 p and miR-365 (24) . There were no previous studies that specifically correlated miR-9 to platelets or explained the exact mechanism by which miR-9 affect megakaryocytopoiesis.…”
Section: Discussionsupporting
confidence: 78%
“…Although this result is in alignment with a study done in 2009 by Landry et al (23) which showed that mRNA translation in blood platelets is regulated by miRNA and that different miRNAs was described to affect biosynthesis of platelets like miR-15 a, miR-339-3 p and miR-365 (24) . There were no previous studies that specifically correlated miR-9 to platelets or explained the exact mechanism by which miR-9 affect megakaryocytopoiesis.…”
Section: Discussionsupporting
confidence: 78%
“…A few studies mapping the full platelet miRNA repertoire have been conducted since then, 24,25 but to our knowledge, no one has studied the platelet miRNA transcriptome in patients with myocardial infarction. In an effort to address this question we conducted RNA-seq of highly purified platelet preparations from patients with STEMI and from healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently published data demonstrates an important role of microRNA in human megakaryocytopoesis [34][35][36][37][38][39]. Despite their lack of nuclear DNA, platelets contain significant amounts of microRNA that have important functions in post-transcriptional gene regulation [37,38,40].…”
Section: Methods For the Assessment Of Platelets Involvement In The Fmentioning
confidence: 99%